Strategies for knowledge management success exploring organizational efficacy - Jennex, Murray E. 1956-; Smolnik, Stefan (Premier reference source, 2011)
"This chapter presents results of a survey looking at how KM practitioners, researchers, KM students, and others interested in KM view what constitutes KM success, including background on KM success and then a series of perspectives on KM/KMS success" - Provided by publisher